From Picture to Text: the Use of Picture in ELT Writing Class - Ika Apriani Fata; Syamsul Bahri; Muridhal Muridhal (Soegijapranata Catholic University, 2018)
Having students to produce an organized and neat piece of writing has always been the life-long dream and goal of all EFL teachers. Thus, many studies have been conducted under quantitative study as like experimental research, to fill in this gap this study focused on figuring out the teacher’s point of view toward the use of picture as media, what are the target and how are the students’ participations toward it based by using qualitative design. The instruments applied are interview, observation and field notes, as triangulation data. One English teacher and 36 EFL learners participated as informants in this research. It turned out that the findings showed that based on interview of the teacher, it is believed that media as alternative to assist teacher in teaching writing. Besides, the teacher seems confident to teach writing by using the picture. Furthermore, the English teacher believed that students developed their writing skill by using picture. Meanwhile, based on observation and field notes, the EFL students seem enthusiast to learn writing especially it is combined with group discussion techniques. As further studies, it is best to look at the students writing assessment process through picture strategies in EFL class.